2014
DOI: 10.1053/j.seminoncol.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Practice Experience With NovoTTF-100A™ System for Glioblastoma: The Patient Registry Dataset (PRiDe)

Abstract: Recurrent glioblastoma multiforme (GBM) is a highly aggressive cancer with poor prognosis, and an overall survival of 6 to 7 months with optimal therapies. The NovoTTF-100A™ System is a novel antimitotic cancer therapy recently approved for the treatment of recurrent GBM, based on phase III (EF-11) trial results. The Patient Registry Dataset (PRiDe) is a post-marketing registry of all recurrent GBM patients who received NovoTTF Therapy in a real-world, clinical practice setting in the United States between 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
101
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 28 publications
10
101
0
Order By: Relevance
“…The compliance with TTFields therapy in the clinical trials was tightly linked to the survival outcomes; monthly compliance above 75% was associated with higher overall survival 9,10,31 . Our cell culture experiments revealed that the surviving cells recover with a delay of 24 h after end of TTFields application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The compliance with TTFields therapy in the clinical trials was tightly linked to the survival outcomes; monthly compliance above 75% was associated with higher overall survival 9,10,31 . Our cell culture experiments revealed that the surviving cells recover with a delay of 24 h after end of TTFields application.…”
Section: Discussionmentioning
confidence: 99%
“…For clinical use they are applied at tumor specific frequencies via ceramic electrodes, so-called transducer arrays, adhered to the shaved scalp of the patient. The therapy compliance was tightly linked to the outcome and monthly compliance above 75% was associated with higher overall survival 9,10 . In addition, this important development in the treatment of GBM patients, the therapy may be further improved by its combination with synergistic therapies.…”
Section: Introductionmentioning
confidence: 99%
“…This trial lead to the approval of the Optune™ system for the treatment of recurrent GBM by the FDA. The analysis of a patient registry dataset (PRiDe) with 457 recurrent GBM patients who were treated with TTFields showed that ≥75% compliance, i.e., application for ≥18 hour per day, was a favourable prognostic factor (Mrugala et al 2014). A recent a Phase III clinical trial (EF-14) of TTFields in patients with newly diagnosed GBM was terminated during interim analysis due to early success (Stupp et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a surface electrical system called Optune that disrupts mitotic spindle formation and cytokinesis has been approved by the FDA for treatment of recurrent GBM after demonstrating survival rates comparable to those achieved with physician's choice chemotherapy [51] and for upfront treatment of GBM after demonstrating a survival advantage when added to standard chemoradiation [2••].…”
Section: Other Targeted Therapies In Gliomasmentioning
confidence: 99%